An exquisite branch–leaf shaped metal sulfoselenide composite endowing an ultrastable sodium-storage lifespan over 10 000 cycles. Issue 32 (5th August 2022) - Zhao, Wenxi; Gao, Lixia; Ma, Xiaoqing; Yue, Luchao; Zhao, Donglin; Li, Zerong; Sun, Shengjun; Luo, Yongsong; Liu, Qian; Asiri, Abdullah M.; Sun, Xuping
Abstract : An exquisite branch–leaf CNF@CoSSe@C was designed and fabricated, which favorably affords rich electrochemistry-active sites and multi-dimensional interconnected ion-transport channels, thus endowing superior sodium-storage lifespan over 13 000 cycles. Abstract : Sluggish Na + -diffusion kinetics and inadequate ion-transport pathways in metal sulfides are one of the dominant bottlenecks for high-efficiency sodium-storage. Introducing hetero-anions into metal sulfides and further exploiting their advanced nanostructures is regarded as an innovative tactic. Herein, taking inspiration from biological systems, a three-dimensional hierarchical "branch–leaf" metal sulfoselenide anode, comprised of MOF-derived carbon-coated CoSSe nanoflake "leaves" and carbon nanofiber intertwined framework "branches" (CNF@CoSSe@C), was designed and fabricated through an electrospinning technique, impregnation growth and a subsequent series of high-temperature heat treatments, which favorably affords superior conductivity and mechanical strength, rich electrochemistry-active sites, multi-dimensional interconnected ion-transport channels, as well as short ion-diffusion distances. These significant advantages together with the exquisite structure are very conducive to highly effective sodium-storage, as attested by attractive specific capacity, impressive rate capability, and ultrastable cyclic lifespan over 13 000 cycles with a capacity fading rate of only 0.01% for every cycle at 20.0 A g −1 . Further dissected by DFT calculations and scan-rate-dependent CV analysis, its superior sodium-storage features are mainly assigned to its significant surface-capacitive behavior and low energy barriers to Na + migration. The remarkable sodium-storage features stimulated us to set up a practical sodium-ion full-cell by matching it with an Na3 V2 (PO4 )3 @C cathode, showing a long-term cyclic lifespan of up to 1000 cycles at 3.0 A g −1 with a high reversible capacity of 156.3 mA h g −1 .